IDENTIFIKASI SUMBER-SUMBER HUKUM INTERNASIONAL DALAM PENANGANAN PENGUNGSI ROHINGYA DI ACEH TAHUN 2025 - Nabila Adzlin Aifha; Devika Rosa Guspita; Aghniya Nurul Hidayah; Tiara Nisa Latifah; Andreas Difa Ananta; Ega Ahmad Noor Hidayah (Gapenas Publisher, 2026)
Rohingya refugees are a refugee group that continues to attract international attention due to discrimination, persecution, and human rights violations in Myanmar. This situation has led to large-scale population migration to various countries in Southeast Asia, including Indonesia. Aceh Province is the region most frequently receiving Rohingya refugees by sea, giving rise to various legal and humanitarian issues that require addressing them in accordance with applicable legal provisions. This study aims to identify the sources of international law that form the basis for handling Rohingya refugees in Aceh in 2025 and analyze their application in Indonesian policy. The research method used is normative juridical research with a legislative approach, a conceptual approach, and a case study approach. The legal materials used consist of primary legal materials in the form of international legal instruments and regulations, as well as secondary legal materials in the form of books, journals, and relevant literature. The research results show that the handling of Rohingya refugees in Aceh in 2025 is based on various sources of international law as stated in Article 38 paragraph (1) of the Statute of the International Court of Justice, namely international treaties, customary international law, general legal principles, court decisions, and expert doctrine. Relevant international treaties include the 1948 Universal Declaration of Human Rights, the 1984 Convention Against Torture, and the 1989 Convention on the Rights of the Child, which provide the basis for protecting the basic rights of refugees. The most influential customary international law is the principle of non-refoulement, which prohibits the return of refugees to areas that could threaten their safety and freedom. In addition, humanitarian principles, international court decisions, and expert doctrine also strengthen the basis for protecting Rohingya refugees. Although Indonesia has not ratified the 1951 Refugee Convention and its 1967 Protocol, the practice of handling Rohingya refugees in Aceh demonstrates the application of international legal norms in national policy through a humanitarian approach and human rights protection